A new species of Rhizocybe (tricholomatoid clade, Agaricales) from Yunnan, China - Ding, Yuxiang; Tian, Enjing; Alvarado, Pablo (Phytotaxa, 2017)
The new species name Rhizocybe alba is proposed here to accommodate some specimens recently collected from Kunming in the Yunnan province of China. The new species has a completely white basidiomata, a compressed and tortuous stipe, and conspicuous white rhizomorphs. A detailed description, drawings and images of the new species are provided, as well as two different phylogenetic analyses based on ITS data and a four-loci (28S and 18S rDNA, tef1, rpb2) DNA sequence alignment.